Government‒business relations in multilevel systems: the effect of conflict perception on venue choice. Issue 5 (3rd September 2017) - Marshall, David; Bernhagen, Patrick
Abstract: In multilevel systems, organised interests, including business firms, can pursue their political goals at different levels. At the same time, national systems of interest representation provide important incentive structures for corporate political behaviour. In this context, corporate political strategy is guided by firms' perceptions of their relationship with policy-makers. If this relationship is under strain in one venue, firms shift their lobbying effort to alternative venues, subject to constraints reflecting national institutional legacies. Using survey data on 56 large German and British firms, the article investigates empirically how perceptions of government‒business relations and national systems of interest representation interact to shape the political behaviour of large firms in multilevel systems. The analysis shows that perceived conflict with public authorities at the national level leads to increased business lobbying at the EU level. Furthermore, national types of interest representation shape relative business engagement at the EU level as well as the readiness of firms to shift venue.